Reciprocal YAP1 loss and INSM1 expression in neuroendocrine prostate cancer. Issue 4 (23rd September 2021) - Asrani, Kaushal; Torres, Alba FC; Woo, Juhyung; Vidotto, Thiago; Tsai, Harrison K; Luo, Jun; Corey, Eva; Hanratty, Brian; Coleman, Ilsa; Yegnasubramanian, Srinivasan; De Marzo, Angelo M; Nelson, Peter S; et al.
Abstract: Neuroendocrine prostate cancer (NEPC) is a rare but aggressive histologic variant of prostate cancer that responds poorly to androgen deprivation therapy. Hybrid NEPC‐adenocarcinoma (AdCa) tumors are common, often eluding accurate pathologic diagnosis and requiring ancillary markers for classification. We recently performed an outlier‐based meta‐analysis across a number of independent gene expression microarray datasets to identify novel markers that differentiate NEPC from AdCa, including up‐regulation of insulinoma‐associated protein 1 ( INSM1 ) and loss of Yes‐associated protein 1 ( YAP1 ). Here, using diverse cancer gene expression datasets, we show that Hippo pathway‐related genes, including YAP1, are among the top down‐regulated gene sets with expression of the neuroendocrine transcription factors, including INSM1. In prostate cancer cell lines, transgenic mouse models, and human prostate tumor cohorts, we confirm that YAP1 RNA and YAP1 protein expression are silenced in NEPC and demonstrate that the inverse correlation of INSM1 and YAP1 expression helps to distinguish AdCa from NEPC. Mechanistically, we find that YAP1 loss in NEPC may help to maintain INSM1 expression in prostate cancer cell lines and we further demonstrate that YAP1 silencing likely occurs epigenetically, via CpG hypermethylation near its transcriptional start site. Taken together, these data nominate two additional markers to distinguish NEPC from AdCa and add to data from other tumor types suggesting that Hippo signaling is tightly reciprocally regulated with neuroendocrine transcription factor expression. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.